FACTORS ASSOCIATED WITH CONTAMINATION OF PUBLIC PARKS (HUÁNUCO, PERÚ) BY TOXOCARA CANIS EGGS AND OTHER ENDOPARASITES OF ZOONOTIC IMPORTANCE - Montalvo-Sabino, Eddyson (2014)
The objective of this work was to evaluate the contamination of public parks in the district of Huánuco, Perú with eggs of Toxocara canis. 32 soil samples were taken in each of 11 parks for a total of 352 samples in May and June of 2014. Parks were selected at random. In each park, 2-3 kg soil was collected according to the double “W” method. Flotation with a saturated sugar solution was used. Samples were considered positive when at least one egg of T. canis was found. Of the 11 parks sampled, T. canis eggs were found in 90.9%. Seven parasites were found along with T. canis in the soil. The sequence of parasite prevalence was in the following descending order: T. canis> Strongylus type eggs of Ancylostoma caninum > A. caninum larvae = Blastocystis hominis > Trichuris vulpis= Entamoeba sp. > Capillaria sp. = Balantidium coli. Parasite richness was 2.45 ± 1.21 (1-4) parasites per public park. Asignificant positive correlation was observed between the area of public parks and parasite richness per public park. No association was found between the condition of the public park and it being positive for T. canis. A dendrogram of similarity of association of parasites present in the 11 public parks showed a greater association between the Strongylus egg type and larvae of A. caninum. Also, a greater similarity existed between T. vulpis, B. coli, Entamoeba sp. and Capillaria sp. T. canis had the lowest similarity with the other parasitic forms. An increase in the prevalence of T. canis was observed in comparison to the previous decade as well as to the presence of other infective parasite stages of public health importance. People and especially children could become contaminated while in public parks and sanitary measures should be taken to control this zoonosis.